Kinetics of Deterioration of the Quality of Purebred Chicken Egg Meal During Storage - Rotinsulu, Merri Diana; Sjaloom Ester Sakul (Faculty of Animal Science Universitas Brawijaya, 2024)
The research objective to determine quality of purebred chicken egg meal deteriorates during storage. The research method used experimental method, counting was a completely randomized design consisting of 5 treatments and 4 replications. As a treatment, the storage time for purebred chicken egg flour at room temperature is formulated as follows T0 (0 days), T1 (10 days), T2 (20 days), T3 (30 days) and T4 (40 days). The variables observed were water content, pH and total microbes. The results of analysis of variance showed that storage time at room temperature had a highly significant different effect (P<0.01) on the water content, pH and total microbes of purebred chicken egg flour. The results of the orthogonal polynomial test show that storage time at room temperature has a highly different linear effect on water content obtained by the equation Y=6.561+0.0177X, linear and quadratic on pH obtained by the equation Y=7.64+0.0095X+0.00015X2 and total microbial colonies of purebred chicken egg flour obtained by the equation Y=2686-0.0172X+0.0006X2. It can be concluded that the kinetics of deterioration in the quality of purebred chicken egg flour occurs 0.25% increase for water content and 0.25 increase for pH and 0.24 log cfu/g increase in the number of bacterial colonies during storage.